Developing Student Worksheets Using Inquiry-based Learning Model with Scientific Approach to Improve Tenth Grade Students Physics Competence - Yulkifli Yulkifli; Rosly Jaafar; Liza Resnita (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
Students' Physics Competencies are not still optimal. One of the causes is the use of student worksheets as the teaching materials that have not yet been suitable for the structure of good student worksheets. In addition, the student worksheets are not developed using the inquiry-based learning model and scientific approach. The purpose of this study is to describe the characteristics and produce valid, practical, and effective student worksheets using the inquiry-based learning model with a scientific approach to improve the tenth-grade students' physics competencies. This research used the Plomp model as the design, which consisted of preliminary research, development or prototyping, and assessment. The data were analyzed using a descriptive percentage technique, describing the student worksheets' validity, practicality, and effectiveness. Based on the preliminary research results, it was found that needs analysis, student analysis, and material analysis were required to be a reference in developing student worksheets using the inquiry-based learning model with a scientific approach. The design stage results show that the student worksheets have been designed using an inquiry-based learning model with a scientific approach. The results of the development phase show that the student worksheets meet the valid criteria of 0.94. The implementation phase results show that the student worksheets meet the very practical criteria based on the teacher's and students' responses, with the percentage of 91.05% and 78.39%, respectively. The results of the evaluation phase show that the student worksheets meet the effective criteria, including attitude (85.81%), knowledge (85.46%), and skills (85.69%). Based on the results of the study, it is concluded that the student worksheets using the inquiry-based learning model with an effective scientific approach to improve the tenth-grade students' physics competencies.